PERCEPTIONS OF STUDENTS ON ACADEMIC DISHONESTY WITHIN THE FRAMEWORK OF THE FRAUD TRIANGLE: AN EMPIRICAL STUDY IN INDONESIA - Nur Laili, Afifah; Sayidah, Nur; Assagaf, Aminullah; Hamdani Alwi Mubarok, Moch; Mohd Nordin, Rumaizah (Proceeding of International Conference on Multidisciplinary Research, 2024)
Fraud is an intentional deception to secure unfair or unlawful gain or to deprive a victim of a legal right. It can occur in any setting, including government, business, and education. Fraud in the realm of education can manifest in various ways, including cheating. Academic cheating is a growing problem that threatens the integrity of our educational system. Fraud in the world of education or academic cheating can be done in various ways including cheating on friends' assignments or exams, exchanging answers, and committing plagiarism. Furthermore, the advancement of technology has made it easier for students to commit fraud by exchanging answers via online applications, looking for answers easily through AI technology, and many others. For that, this study aims to determine student perceptions of academic fraud based on the Fraud Triangle elements which are pressure, opportunity, and rationalization. The research is conducted quantitatively using a questionnaire survey via Google form to 82 respondents and analysed using descriptive analysis. The research utilised the convenience sampling method, where respondents consisted of students from all over Indonesia who were divided into business and non-business students. The results of an analysis of 82 respondents from public and private universities in Surabaya, show that even though students are under any pressure, students still choose not to cheat because they know it violates religious teachings, which is evidenced by the additional variable, namely the duration of prayer, which shows dominance on a scale of 1. and 3. It is expected that the findings of the research will be taken into consideration for the implementation of examinations in the world of education, especially in higher education to make a policy that can reduce cheating.